Organizational Performance Evaluation Maysan Water Directorate - Case Study - مكطوف, هنادي صكر; حسين, اشواق علي (Journal of Economics and Administrative Sciences, 2020)
The research aims to improve the performance of the Directorate of Maysan water by reconciling the objectives of the employees of the directorate with the objectives of the Directorate itself, as well as to identify the strengths and weaknesses in the performance of the Directorate (Leadership - Individuals - Knowledge - Operations - Financial) and presented to experts and arbitrators of specialized, and the researchers have relied on the case study methodology as a descriptive approach is comprehensive analysis, and draws on more than one approach, method and scientific design, has been interviewed a number of experts in the Directorate Maysan's water Identify the weaknesses and strengths of the Directorate, the research has reached a number of results, the most important of which is that the Directorate of Maysan water has no awareness of the importance of the evaluation process and it lacks a system for evaluating its performance and that the evaluation programs that are conducted in the Directorate are limited to conducting a formative evaluation and the level of individual performance only The research came out with a number of recommendations, the most important of which should be the vision and mission of the Directorate clear and written to all employees in the Directorate, which requires to be awareness campaigns to do so, so that the objectives of employees linked to the objectives of the Directorate.